CoFe2O4 nanoparticles dispersed on carbon rods derived from cotton for high-efficiency microwave absorption. (21st May 2022) - Xu, Jiajun; Liu, Dong; Meng, Yubo; Tang, Shiyu; Wang, Fei; Bian, Chao; Chen, Xiaoyue; Xiao, Siren; Meng, Xiuxia; Yang, Naitao
Abstract: Biomass-derived carbon materials have received a surge of scientific attention to develop lightweight and broadband microwave absorbers. Herein, rodlike porous carbon materials derived from cotton have been fabricated with uniformly dispersed CoFe2 O4 nanoparticles via facile and scalable process. The combination of magnetic particles and carbonaceous material is advantageous to realize the magnetic-dielectric synergistic effect which could effectively promote the dissipation of incident waves, giving rise to an optimal reflection loss value of –48.2 dB over a qualified bandwidth (4.8 GHz) at 2.5 mm. The cotton-derived carbon rods with conductive network not only act as a supporter to carry the CoFe2 O4 nanoparticles, but also provide massive heterointerfaces to facilitate the interfacial polarization. In consideration of the renewable and abundant resource of cotton, the as-prepared CoFe2 O4 /C composites would meet the increasing demand of lightweight and highly efficient microwave absorbers.